The Impact of Political Institutions on General Insurance/ Takaful Consumption: A Comparative Study Between OIC Countries and Non-OIC Developing Countries - Mohamad, Mohammad Taqiuddin; Noordin , Kamaruzaman; Mahani, Mohammad Ghaith (Online Journal of Research in Islamic Studies, 2022)
Political institutions are part of the overall institutional matrix of a country and cover institutions that are responsible for establishing and maintaining a robust and reliable political system. The impact of an instable political system on general insurance/ Takaful services demand in OIC countries is an area that has not been sufficiently explored in the literature. This study is set to empirically test the impact of political institutions on general insurance/ Takaful consumption in OIC countries versus non-OIC developing countries. To address the research question, fixed effects and random effects models are applied on a strongly balanced dataset covering 36 OIC countries and 67 non-OIC developing countries for the years from 1994 till 2015. The study used two different indicators of political institutions. Namely, the control of corruption index and the government effectiveness index which are retrieved from the World Governance Indicators (WGI). The study utilises insurance density rate as a dependent variable. Further, for more robust findings, the researchers utilise general insurance penetration rate as well. The results suggest that better political institutional environment would play a role in promoting general insurance/ takaful consumption only in OIC countries but not necessarily in non-OIC developing countries. This finding further illustrates the unique institutional environment in OIC countries. This paper recommends that policy makers look into the potential of integrating takaful services in the insurance industry especially in OIC countries that still do not offer Islamic financial services.